1974
DOI: 10.1530/acta.0.075s074
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Dogs for Studies of Toxicity of Contraceptive Hormones

Abstract: Responses to endogenous and exogenous sex steroids in the dog are characteristic for that species, differing in many important aspects from other laboratory animals and man. Long-term administration to dogs of progesterone and synthetic compounds structurally related to this natural gestagen has resulted in precocious development of mammary gland tumours and other changes suggesting stimulation of anterior pituitary activity. Progestogens structurally related to testosterone have not induced similar effects. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1975
1975
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Initial findings indicated that synthetic progestins derived from 19-nortestosterone stimulate mammary tumor development in the dog only weakly or not at all [1,3,19]. The difference in tumorigenicity of these two classes of progestins has been attributed to differences in progestin activity, as reflected by their transformative potency in the endometrium, the 17c~-hydroxyprogesterone derivatives being much more potent in the dog than are the 19-nortestosterone derivatives [19][20][21].…”
Section: Contraceptive Steroids and Mammary Neoplasia: Animal Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Initial findings indicated that synthetic progestins derived from 19-nortestosterone stimulate mammary tumor development in the dog only weakly or not at all [1,3,19]. The difference in tumorigenicity of these two classes of progestins has been attributed to differences in progestin activity, as reflected by their transformative potency in the endometrium, the 17c~-hydroxyprogesterone derivatives being much more potent in the dog than are the 19-nortestosterone derivatives [19][20][21].…”
Section: Contraceptive Steroids and Mammary Neoplasia: Animal Studiesmentioning
confidence: 99%
“…The difference in tumorigenicity of these two classes of progestins has been attributed to differences in progestin activity, as reflected by their transformative potency in the endometrium, the 17c~-hydroxyprogesterone derivatives being much more potent in the dog than are the 19-nortestosterone derivatives [19][20][21]. In humans, however, CS derived from 19-nortestosterone have greater progestin activity than do those derived from 17o~-hydroxyprogesterone [21].…”
Section: Contraceptive Steroids and Mammary Neoplasia: Animal Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Such understanding is important because animal testing requirements for hor¬ monal contraceptives and for progestagens and oestrogens used over long periods for non-contra¬ ceptive purposes include long-term toxicity studies in the dog. Certain progestagens used for human contraception have led to mammary gland changes in the dog, including enhanced occurrence of mammary gland neoplasia (Goldzieher & Kraemer, 1972; Wazeter, Geil, Berliner & Lamar, 1973;Hill & Dumas, 1974). The fact that the changes in the mammary gland have been found almost exclusively in the dog, rather than in rats, monkeys and man, has led to the assumption that the pro¬ gestagens concerned are progestationally very active in the dog (Hill, Averkin, Brown, Gagne & Segre, 1970;Graf, El Etreby, Richter, Günzel & Neumann, 1975;Haase, Beier, Hartmann & Elger, 1977), or that the canine mammary and/or anterior pituitary gland is very sensitive to progestagens (Neumann & Elger, 1972).…”
Section: Introductionmentioning
confidence: 99%